Recurrent Oral Squamous Papilloma in a HIV Infected Patient: Case Report - Reis, Helena Lucia Barroso dos; Passos, Mauro Romero Leal; Helena, Aluízio Antônio de Santa; Cavalcante, Fernanda Sampaio; Júnior, Arley Silva; Ferreira, Dennis de Carvalho (IntechOpen, 2012)
None